Tokey Sambal Hitam: Sambal Hitam Mek Tok / Raja Nurul Izzah Raja Ismail and Hanisah Zainol Abiddin - Raja Ismail, Raja Nurul Izzah; Zainol Abiddin, Hanisah (2022)
Sambal Hitam Mek Tok offers sambal product food to give satisfaction to the customers by tasting a spiciness of sambal hitam itself. It is identifying the people who wants to eat spicy sambal as their side dish while eating their main course. It is affordable price product with a good quality. Thus, our product was targeting for the children, family, and students. Sambal Hitam Mek Tok’s marketing strategy is to emphasize the quality and price of product in large quantity. It offers the affordable price because many people especially students want to buy this product and the best thing is we do cover all Malaysia. Hence, we develop marketing strategy that gives attraction to buy our Sambal Hitam Mek Tok. The taste is delicious, the price is low, and the product is high quality. Soft-sell and hard-sell copywriting are two types of copywriting that we create to attract our customers in our Facebook pages. By providing a teaser, we hope that it will get the attention of Facebook users who are interested in looking for our Sambal Hitam. These strategies are implemented in order to attract more customers and encourage them to purchase our goods. Tokey is a person in charge of Sambal Hitam HQ's management. We created a Facebook page to help us grow our business through social media, and we learned how to write teaser posts, soft sells, and hard sells on Facebook. To avoid profit drops, we also need to increase revenue to at least RM61 and judicious expenditure for our goods. In Malaysia, we need to promote the goods using social media.